Determinación de la frecuencia de apareamiento en la abeja cleptobiótica Lestrimelitta niitkib (Apidae, Meliponini) mediante el uso de microsatélites - Guerrero-García, Eloísa; Solórzano-Gordillo, Erik; Sánchez, Daniel (Instituto de Ecología, A.C., 2014)
In this paper we determined the mating frequency in the cleptobiotic bee Lestrimelitta niitkib by microsatellite typing. We found 6 queens to be singly mated while only one mated twice. We confirm this genus to be mainly single mated.